Studi Eksplanatif Penyebab Gerakan Separatis Minoritas Muslim Moro di Filipina - Hasanah, Eva Putriya (Journal of Integrative International Relations, 2017)
This qualitative research aims to analyze the cause of the spatial movements perpetrated by the Moro Muslim community in Southern Philippines. This departs from the writer's assumption that the separatist movement is not merely a desire for secession but of other factors driving the movement of the separatist movement. The results of the analysis in this study indicate that there are three things that cause Muslim societies Moro do separatist movement. First, there is bad experience in the context of history. Initially, the Muslim community was the majority in the Philippines, but after the arrival of the Spanish to colonize the Philippines there were apostasy actions that were carried out in various ways so that in the end the Filipino Muslims became a minority. In addition, during the colonial period the United States had imposed all discriminative policies against Muslims. Second, the existence of a series of crimes against humanity experienced by post-independence Philippine Muslims, including jabidah, upi, barrio, and buldon event that shows violence against Muslims. Third, there is a failure of efforts by the government to resolve the conflict in the Southern Philippines. This is marked by the failure of the government to grant autonomy rights to Muslim areas because it continues to participate in development in the region but does not provide for the welfare of the Muslim community. In fact, the data indicate social inequality between areas that show that Moro Muslims are in the poorest position.